2008
DOI: 10.1089/dia.2007.0294
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Human and Bovine Insulin in Type 1 Diabetes Mellitus Patients

Abstract: Bovine and human insulins are antigenic, and there is no significant difference in AIAB titer. Prospective studies are required to determine the long-term clinical significance of these antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…Upon retrospective analysis, we found that these antibodies appeared early, during the first 4-month trial after the end of the first month of leptin administration, and further increased thereafter. The appearance of antibodies following a substitutive hormonal therapy has been reported with other recombinant proteins (22)(23)(24)(25)(26)(27), and it can suggest some mechanisms for the resistance reported here. In type 1 diabetic patients, the production of antibodies against insulin is common but without reported clinical relevance, and has been observed with bovine, porcine, and recombinant insulin (25)(26)(27).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Upon retrospective analysis, we found that these antibodies appeared early, during the first 4-month trial after the end of the first month of leptin administration, and further increased thereafter. The appearance of antibodies following a substitutive hormonal therapy has been reported with other recombinant proteins (22)(23)(24)(25)(26)(27), and it can suggest some mechanisms for the resistance reported here. In type 1 diabetic patients, the production of antibodies against insulin is common but without reported clinical relevance, and has been observed with bovine, porcine, and recombinant insulin (25)(26)(27).…”
Section: Discussionsupporting
confidence: 75%
“…The appearance of antibodies following a substitutive hormonal therapy has been reported with other recombinant proteins (22)(23)(24)(25)(26)(27), and it can suggest some mechanisms for the resistance reported here. In type 1 diabetic patients, the production of antibodies against insulin is common but without reported clinical relevance, and has been observed with bovine, porcine, and recombinant insulin (25)(26)(27). Antibody production interfering with the treatment effect has been well documented in children with congenital GH deficiency (22)(23)(24).…”
Section: Discussionsupporting
confidence: 75%